(untitled) (Archives of Criminology, 2023)
For many years the Russian Federation has had one of the highest numbers of people incarcerated in penal institutions (per 100,000 population). As of 1 January 2020, there were 523,928 people in prison. An analysis of the legislation and the practice of its application reveals that the main trend of modern Russian penal policy is for stricter penalties, longer prison terms, and inefficient use of alternative punishments. The ongoing trend of humanising and liberalising criminal justice remains virtually invisible and suppressed by a repressive bias, which ultimately prevents it from significantly influencing the overall direction of state policy in this area.